Komunikasi Orang Tua Dan Anak Tunarungu Wicara Pada Kotak Menara Bekasi - Muhammad Syafiq; Mayasari; Tri Susanto (KOMVERSAL, 2024)
Speech deaf children have limitations in communication and interaction. Parents play an important role in supporting children with special needs in overcoming these limitations through adaptive and innovative communication patterns. Therefore, the purpose of this research is to know and understand how the application of communication between parents and children with special needs (ABK), especially children with speech deafness in Kotak Menara. This study uses a qualitative approach and phenomenological research method and utilizes Herbert Blumer's symbolic interaction theory to explore how parents and children understand each other and build meaning through their social interactions. The results show that the communication experience between parents and children with disabilities is not just an exchange of information, but also a process of forming deep meaning. They combine verbal and non-verbal communication to deal with the challenges posed by their children's limited ability to communicate.Keywords: Deaf children with speech impairment, verbal and non-verbal communication, Kotak Menara